Integrated multi-scale approaches to Mediterranean grasslands. A case-study on the Nebrodi Mounts (Sicily) - Mingo A.; Migliozzi A.; Maugeri G. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
An integrated multi-scale research project was implemented on the pastures of the Nebrodi Mounts, a protected area situated on the north-eastern side of Sicily. This study included landscape analysis through GIS techniques, community structure reconstruction by field sampling, and individual-based experimental tests performed on selected species. The results of this work allowed landscape units to be differentiated for their specific attributes, including soil, climate, water availability, erosion risks, biodiversity, feeding value, and potential for alternative exploitation. Six main community types were identified, each related to different soil and climate conditions or to land history and grazing intensity. Guidelines for pasture exploitation are presented, according to their feeding values, resilience levels and environmental qualities. The routine implemented for this research may provide new tools for a sustainable grassland exploitation as well as for environment protection and enhancement.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)